Pendidikan Islam Dalam Konteks Kolonialisme dan Pasca-Kolonialisme - mindani; Azizah Aryati; Titin Sumarni; Derna Wati; Jasrin Abito (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Islamic education in Indonesia has a long history closely linked to the nation's socio-political dynamics, from the era of Islamic kingdoms, colonialism, to the post-colonial era. During the Islamic kingdoms, education served as a center for preaching, moral formation, and the dissemination of knowledge. With the arrival of Dutch colonialism, the Islamic education system came under severe pressure due to secular policies and colonial political control that limited the role of Islamic institutions. Nevertheless, Islamic scholars and figures continued to play a crucial role in maintaining the identity and independence of Islamic education through Islamic boarding schools (pesantren) and madrasahs (Islamic boarding schools). Post-colonialism brought new challenges in the form of modernization and globalization, which demanded the integration of religious and general knowledge. Through a qualitative approach and literature review, this study aims to analyze the development of Islamic education from a historical perspective, focusing on the era of Islamic kingdoms, colonialism, and its transformation in the post-colonial era. The results show that Islamic education is highly adaptable to social and political change and contributes significantly to the formation of the character of the Indonesian nation.